Longitudinal associations of family burden and patient quality of life in the context of first-episode schizophrenia in the RAISE-ETP study. (June 2019) - Nuttall, Amy K.; Thakkar, Katharine N.; Luo, Xiaochen; Mueser, Kim T.; Glynn, Shirley M.; Achtyes, Eric D.; Kane, John M.
Highlights: Covariation in change over time occurs between family burden and patient quality of life. Family burden, quality of life, and positive symptoms improved over time. Baseline level of patient quality of life and positive symptoms were not associated with change in family burden. Baseline level of family burden was not associated with changes in patient quality of life or positive symptoms. Abstract: The present study examined longitudinal associations between family member perceived burden and clinical correlates to understand potential covariation in change over time in the context of first-episode schizophrenia in the RAISE-ETP study ( N  = 282). Across 24 months, family burden, patient quality of life, and positive symptoms improved. Findings from the present study suggest covariation in change over time in quality of life and family burden. As patient quality of life improved, family burden decreased. However, initial levels of quality of life were not significantly associated with changes in family burden and vice versa. Initial levels of positive symptoms were significantly associated with initial levels of family burden. These findings have treatment implications by suggesting the potential for interventions aimed at improving quality of life to have a spillover effect on family burden, or alternatively, that reducing perceived family burden may improve patient quality of life.